Fenomena Narsisme Muslimah dalam Aplikasi Tiktok: Analisis Semiotika Charles William Morris - Fatimah, Siti; Syadzali, Ahmad (Jurusan Aqidah dan Filsafat Islam Fakultas Ushuluddin dan Adab UIN Sultan Maulana Hasanuddin Banten, 2022)
The study explores exictence of Muslim Women in Social Media to shows theirselves. The emergence of the TikTok application affects the emergence of narcissistic behavior in everyone, including Muslim women. Narcissistic individuals are always self-conscious about their appearance and uploaded pictures of themselves in various settings in an effort to attract attention and admiration from others. Accordingly, the goals and research questions are outlined in two focus discussions: how prevalent Muslim narcissism is in the TikTok application today, and how can we determine the message or hidden meaning of Muslim TikTok content using Charles William Morris' triadic theory (triangle) through observation and documentation of the accounts of three Muslim women who actively use TikTok. The findings of this study revealed narcissistic traits in three Muslim users of the TikTok app named Nabila, Herlin Kenza, and Mila Alawiyah. The narcissistic inclination results from a persistent desire to stand out, from displaying a high-class lifestyle, from giving significant importance to physical beauty in daily life, and from consistently displaying expensive and branded items. All of that is shown and displayed with an excessive amount of self-confidence, which results in arrogant behavior.